Protective Functions of Reactive Astrocytes Following Central Nervous System Insult - Linnerbauer, Mathias; Rothhammer, Veit (Frontiers in Immunology, 2020)
Astrocytes play important roles in numerous central nervous system disorders including autoimmune inflammatory, hypoxic and degenerative diseases such as Multiple Sclerosis, ischemic stroke and Alzheimer’s disease. Depending on the spatial and temporal context, activated astrocytes may contribute to the pathogenesis, progression, and recovery of disease. Recent progress in the dissection of transcriptional responses to varying forms of central nervous system insult has shed light on the mechanisms that govern the complexity of reactive astrocyte functions. While a large body of research focuses on the pathogenic effects of reactive astrocytes, little is known about how they limit inflammation and contribute to tissue regeneration. However, these protective astrocyte pathways might be of relevance for the understanding of the underlying pathology in disease and may lead to novel targeted approaches to treat autoimmune inflammatory and degenerative disorders of the central nervous system. In this review article, we have revisited the emerging concept of protective astrocyte functions and discuss their role in the recovery from inflammatory and ischemic disease as well as their role in degenerative disorders. Focusing on soluble astrocyte derived mediators, we aggregate the existing knowledge on astrocyte functions in the maintenance of homeostasis as well as their reparative and tissue-protective function after acute lesions and in neurodegenerative disorders. Finally, we give an outlook of how these mediators may guide future therapeutic strategies to tackle hence untreatable disorders of the central nervous system.